2018
DOI: 10.1038/s41426-018-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid rise of the ESBL and mcr-1 genes in Escherichia coli of chicken origin in China, 2008–2014

Abstract: Extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-EC) strains are emerging around the world as a source of resistance to β-lactam antibiotics such as ampicillin, cefotaxime, and ceftazidime. mcr-1 is a novel plasmid-mediated gene conferring resistance to colistin. The aim of this study was to investigate the prevalence of ESBL-EC mcr-1 of chicken origin in the different provinces of China during 2008–2014. Overall, 341 of 821 isolates were determined to be ESBL-EC strains, and the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
96
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 50 publications
16
96
5
Order By: Relevance
“…The high diversity of the mcr-1-positive E. coli and K. pneumoniae isolates detected in the present study corresponds to the results for mcr-positive Enterobacteriaceae isolated from different sources (food, animals, and humans) in other studies (Zurfluh et al, 2016;Luo et al, 2017;Roschanski et al, 2017;Zurfluh et al, 2017;El Garch et al, 2018). However, some studies have described an increased prevalence of E. coli with mcr-1 belonging to ST10 obtained from food animals, food, and humans (Zurfluh et al, 2016;El Garch et al, 2018;Shen et al, 2018;Wu et al, 2018). Similarly, E. coli isolates found here belonging to ST10 (n = 5) and ST744 (n = 5) were most often detected.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high diversity of the mcr-1-positive E. coli and K. pneumoniae isolates detected in the present study corresponds to the results for mcr-positive Enterobacteriaceae isolated from different sources (food, animals, and humans) in other studies (Zurfluh et al, 2016;Luo et al, 2017;Roschanski et al, 2017;Zurfluh et al, 2017;El Garch et al, 2018). However, some studies have described an increased prevalence of E. coli with mcr-1 belonging to ST10 obtained from food animals, food, and humans (Zurfluh et al, 2016;El Garch et al, 2018;Shen et al, 2018;Wu et al, 2018). Similarly, E. coli isolates found here belonging to ST10 (n = 5) and ST744 (n = 5) were most often detected.…”
Section: Discussionsupporting
confidence: 89%
“…The dissemination of mcr genes in gram-negative bacteria isolated from food-producing animals and from food in Asian countries (Kawanishi et al, 2016;Liu et al, 2017;Wu et al, 2018) was confirmed by the detection of E. coli and C. braakii with the mcr-1 gene in two samples of rabbit meat imported from China. The examined rabbit meat samples from Hungary and the Czechia did not contain bacteria with mcr genes.…”
Section: Discussionmentioning
confidence: 88%
“…The bla TEM were the most prevalent beta-lactamase in this study, which is similar to a study on hospital wastewater in Brazil (85). However, this is in contrast with other findings with bla CTX-M being the most frequent ESBL genes from various samples including in hospital effluent, surface water and WWTPs (34, 39, 86). This result was confirmed by qPCR data performed in another study in the framework of the StARE project which showed the detection of bla TEM genes, where bla SHV and bla CTX-M group 1 were not detected (22).…”
Section: Discussioncontrasting
confidence: 99%
“…Even more striking were the extremely high levels of the mobile colistin resistance gene mcr in our E. coli isolates. The ST101 lineage which dominated our isolate collection has been identified as a driving lineage in the emergence of ESBL-Ec, and mcr positive E. coli in the region [36], but we observed the mcr gene across a large number of lineages, a finding which may be of substantial importance. This confirms earlier reports showing that travel exacerbates the global spread of not only ESBL genes but also E. coli strains carrying mobile colistin resistance genes [37].…”
Section: Discussionmentioning
confidence: 64%